A randomized controlled trial to examine the effectiveness of the Dutch version of the Program for the Education and Enrichment of Relational Skills (PEERS®) - Sakinah Idris; Bjorn Jaime van Pelt; Gabrine Jagersma; Jorieke Duvekot; Athanasios Maras; Jan van der Ende; Neeltje van Haren; Kirstin Greaves-Lord (BMC Psychiatry, 2022)
Abstract Background This study examines the effectiveness of the culturally adapted Dutch version of The Program for the Education and Enrichment of Relational Skills (PEERS®), utilizing a randomized control trial (RCT) with an active treatment control condition. Methods 106 adolescents with ASD, aged 12–18 years, were randomly assigned to one of two group interventions: the experimental condition (PEERS®; n = 54) or the active treatment control condition (Regulation, Organization and Autonomy Didactics; ROAD; n = 52). Effects of interventions on social skills were primarily assessed using an observational measure (CASS – Contextual Assessment Social Skills). Secondary indices of social skills were self, parent and teacher reported questionnaire data (i.e., Social Responsiveness Scale; SRS, and Social Skills Improvement System; SSIS). Treatment satisfaction was also obtained from adolescents and their parents. Results Results on the observational measure of social skills revealed improvements in positive affect, overall quality of rapport, as well as starting and ending a conversation, irrespective of condition. Compared to ROAD, PEERS® participants showed increased overall self-reported social skills (SSIS). Parent reports showed decreased overall social skill impairment (SRS) as well as improved social communication (SSIS subscale), with significantly more progress in the PEERS® group. Furthermore, parents of adolescents in the PEERS® group were significantly more satisfied with the intervention (M = 8.20, SD = 1.46) than parents of adolescents in the ROAD group (M = 7.52, SD = 1.45). The self-reported treatment satisfaction of adolescents did not differ between conditions. Teacher data showed decreased social skill impairment as measured with the SRS, irrespective of condition. Conclusions This study reveals promising indications that the Dutch version of PEERS® enhances social skills in adolescents with ASD. Yet, further research is needed into how effectiveness can be optimized. Trial registration Dutch trail register NTR6255 (NL6117) 08/02/2017 https://www.trialregister.nl/trial/6117